2011
DOI: 10.7150/ijbs.7.347
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21 plays an Important Role in Radiation Induced Carcinogenesis in BALB/c Mice by Directly Targeting the Tumor Suppressor Gene Big-h3

Abstract: Dysregulation of certain microRNAs (miRNAs) in cancer can promote tumorigenesis, metastasis and invasion. However, the functions and targets of only a few mammalian miRNAs are known. In particular, the miRNAs that participates in radiation induced carcinogenesis and the miRNAs that target the tumor suppressor gene Big-h3 remain undefined. Here in this study, using a radiation induced thymic lymphoma model in BALB/c mice, we found that the tumor suppressor gene Big-h3 is down-regulated and miR-21 is up-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(90 citation statements)
references
References 69 publications
3
87
0
Order By: Relevance
“…Detection is based on a click reaction [20], a copper catalyzed covalent reaction between an azide and an alkyne. Flow Cytometry Assay was performed by using CellQuest software (Becton Dickinson, Franklin Lakes, NJ, USA) as described previously [21,22]. For MTT assay, 500 cells per well were seeded in triplicate in a 96-well plate with complete growth medium.…”
Section: Methodsmentioning
confidence: 99%
“…Detection is based on a click reaction [20], a copper catalyzed covalent reaction between an azide and an alkyne. Flow Cytometry Assay was performed by using CellQuest software (Becton Dickinson, Franklin Lakes, NJ, USA) as described previously [21,22]. For MTT assay, 500 cells per well were seeded in triplicate in a 96-well plate with complete growth medium.…”
Section: Methodsmentioning
confidence: 99%
“…Ectopic expression of miR-21 increased radioresistance and inhibition of miR-21 by the PNA anti-miR-21 [25]. The radioresistance was caused by miR-21 directly targeting BIGH3, a transforming growth factor that is overexpressed in various types of cancer [25][26][27].…”
Section: Discussionmentioning
confidence: 98%
“…The radioresistance was caused by miR-21 directly targeting BIGH3, a transforming growth factor that is overexpressed in various types of cancer [25][26][27]. Wagner-Ecker et al reported that radiation increased miR-21 expression in human endothelial cells, suggesting an important role of miR-21 in improving the clonogenic survival of cancer cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Then these mice were routinely cared and observed daily. All mice were housed in a Specific Pathogen-Free (SPF) facility for all experiments [4,5,22,23,24]. All animal experiments were undertaken in accordance with the National Institute of Health "Guide for the Care and Use of Laboratory Animals" (NIH Publication No.…”
Section: Methodsmentioning
confidence: 99%